Comparative study of the structural and rheological properties of PA6 and PA12 based synthetic talc nanocomposites. (7th April 2015) - Beuguel, Quentin; Ville, Julien; Crepin-Leblond, Jérôme; Mederic, Pascal; Aubry, Thierry
Abstract: The structural and rheological properties of synthetic talc/polyamide (ST/PA) composites, elaborated by simultaneous melt mixing of a PA6 or PA12 matrix and a hydrogel filled with talc, were studied, focusing on the difference between PA6 and PA12 based nanocomposites. The structure of ST/PA composites is shown to be largely composed of nanometric particles. However, the presence of few micrometric aggregates is shown at moderate solid volume fractions, for both PA6 and PA12. The results also show that PA6 matrix is more efficient than PA12 matrix to disperse synthetic talc nanoparticles; the difference in matrix effect is discussed in terms of matrix polarity, PA chain radius of gyration and role played by water brought by the hydrogel. Finally, the results of the present study suggest that the structural and rheological properties of ST/PA are close to those of organically modified montmorillonite/PA nanocomposites, especially when PA6 is the matrix. Graphical abstract: Highlights: New nanocomposites based on PA were prepared from a hydrogel of synthetic talc. Influence of matrix (PA6 or PA12) was studied on structure and rheology. PA6 matrix improves the dispersion state of synthetic talc nanoparticles. This improvement is mainly attributed to the polarity of the PA6 matrix. Synthetic talc/PA6 materials could rival modified montmorillonite/PA6 nanocomposites.